Health and health care of the preschool child in Hout Bay - Delport, S V (Department of Paediatrics and Child Health, 2018)
At present not enough is known about the health of preschool children in the poorer communities of Cape Town. This study, was undertaken to assess the health and health care of preschool children in one such community: that of the Hout Bay harbour township. A clinic and community-based surveillance programme was devised to make this assessment. Data were obtained by monitoring the records at the Community Health Centre in the township. A study sample of 214 children from the community was also selected by random stratified cluster sampling. This sample was assessed by means of a questionnaire and a full physical examination. Analysis of data was performed on the IBM main-frame computer. A large number of medical problems were identified on screening the community sample. Most of these problems were minor ones and could be managed appropriately at the Health Centre. On the basis of the referral patterns and the small number of newly diagnosed functionally important health problems, the provision of health care in-the area was considered to be adequate. The high immunisation rate in the preschool children and the excellent attendance figures at the child health clinics indicates that the services provided are well utilised by the population. Dental caries was found to be a major health problem in the area. A strong case for the introduction of a dental health educational programme and for the fluoridisation of drinking water can made on the basis of these findings. An ongoing health screening programme would be beneficial. It could be accomplished by utilising appropriately trained nursing personnel.